SISTEM PAKAR DIAGNOSA PENYAKIT DAN PENENTUAN JENIS OBAT TRADISIONAL SEBAGAI ALTERNATIF PENYEMBUHAN - -, Suraya (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
This research was conducted based on the need for a tool for community useful in diagnosing the disease in human being. This tool is an expert system which using Visual Basic 6.0. This expert system is used to diagnose and also able to provide medical advice. Inference method used is forward chaining with the model of Depth First Search. The output of this system in the form of the name of the disease and treatment suggestions.